The Effect of Contrast Therapy on Phlebitis Severity in Toddlers and Preschoolers: A Clinical Study at Cibabat Hospital, Cimahi - Apriany, Dyna; Delima, Elga; Setiawan, Asep; Ardiansyah, Diki (STIKep PPNI Jawa Barat, 2025)
Background: Phlebitis remains a prevalent complication associated with intravenous therapy in pediatric populations, particularly among toddlers and preschool-aged children. Managing phlebitis effectively is essential to minimize discomfort and prevent further complications. Non-pharmacological interventions, such as contrast therapy which involves alternating applications of warm and cold compresses have shown potential in reducing local inflammation and improving patient outcomes. Objective: This study aimed to assess the effectiveness of contrast therapy in reducing phlebitis severity among young children receiving intravenous treatment at a public hospital in Indonesia. Methods: A quasi-experimental study was conducted using a non-equivalent control group design with pretest and posttest assessments. A total of 30 pediatric patients diagnosed with phlebitis were recruited and allocated to either the intervention group (contrast therapy) or the control group (cold compress only). Phlebitis severity was evaluated using the Visual Infusion Phlebitis (VIP) Scale. Statistical analyses included the Wilcoxon signed-rank test and Mann–Whitney U test for bivariate comparisons, and logistic regression for multivariate analysis. Results: The application of contrast therapy significantly reduced the phlebitis grading scale within the intervention group. However, when comparing the intervention and control groups, the difference in mean phlebitis score reduction was not statistically significant. Conclusion: Contrast therapy serves as an effective non-pharmacological approach to managing phlebitis in pediatric patients. Nonetheless, its clinical effectiveness in comparison to cold compress therapy alone appears comparable. Further research with larger sample sizes and randomized designs is recommended to validate these findings and optimize clinical practice.